Study of the influence of structural modification of ZrO2 ceramics on resistance to hydrogen absorption and gas swelling processes - Kozlovskiy, Artem (International Journal of Mathematics and Physics, 2024)
The main purpose of this work is to study the influence of structural modifications in ZrO2 ceramics on the resistance to hydrogenation processes arising as a result of testing the performance of ceramics as materials for solid oxide fuel cells. During the studies conducted it was established that the use of stabilizing MgO and CaCO3 additives to initiate the polymorphic transformation processes in ZrO2 ceramics makes it possible to enhance the resistance of ceramics to hydrogen swelling due to the stabilization of the crystal structure, the change of which is associated with polymorphic transformations. Suppression of volumetric swelling processes due to polymorphic transformations caused by the addition of stabilizing additives made it possible to elevate resistance to hydrogen absorption and destabilization of the near-surface layer by preventing hydrogen agglomeration processes in the near-surface layer. It has been determined that the modification of ZrO2 ceramics by initializing the polymorphic transformation processes of the m-ZrO2 → t – ZrO2 and m-ZrO2 → c-ZrO2 type leads not only to an elevation in strength parameters, but also to an increase in resistance to embrittlement processes during hydrogenation and high-temperature degradation. Keywords: ZrO2 ceramics, gas swelling processes, modification, mechanochemical solid-phase synthesis, polymorphic transformations.